1997
DOI: 10.1021/jf970454o
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Extraction of Taxanes from Taxus Biomass

Abstract: A method is presented for the extraction of the taxane class of natural products, including paclitaxel, from Taxus needles using microwave-assisted extraction (MAE). Various temperatures, times, and organic solvents for the MAE procedure were investigated to optimize the efficiency of the extraction. The effects of biomass to solvent ratio and the water content of the system on taxane recovery were also determined. Under appropriate MAE conditions using 95% ethanol, an extract of the needles was obtained which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…Limitations of existing extraction methods, such as high energy consumption (more than 10 % of total process required energy) and usage of harmful chemicals, have forced food and chemical industries to find new "green" separation techniques which typically use less solvent and energy, such as microwave extraction (MAE), supercritical fluid extraction, ultrasound extraction (Ping et al 2010;Vellingiri et al 2011). Microwaves have been used for the extraction of some biological compounds, such as extraction of essential oils from the leaves of rosemary and peppermint (Chen and Spiro 1994), extraction of glycyrrhizic acid from licorice root (Pan et al 2000), extraction of taxanes from Taxus biomass (Mattina et al 1997) and extraction of ergosterol and total fatty acids from fungal hyphae and spores, mushrooms, filtered air, artificially contaminated corn, naturally contaminated grain dust, and soil (Young 1995). Also, Pan et al (2003) have found that MAE extraction improves the efficiency of the extraction of polyphenols and caffeine from green tea leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations of existing extraction methods, such as high energy consumption (more than 10 % of total process required energy) and usage of harmful chemicals, have forced food and chemical industries to find new "green" separation techniques which typically use less solvent and energy, such as microwave extraction (MAE), supercritical fluid extraction, ultrasound extraction (Ping et al 2010;Vellingiri et al 2011). Microwaves have been used for the extraction of some biological compounds, such as extraction of essential oils from the leaves of rosemary and peppermint (Chen and Spiro 1994), extraction of glycyrrhizic acid from licorice root (Pan et al 2000), extraction of taxanes from Taxus biomass (Mattina et al 1997) and extraction of ergosterol and total fatty acids from fungal hyphae and spores, mushrooms, filtered air, artificially contaminated corn, naturally contaminated grain dust, and soil (Young 1995). Also, Pan et al (2003) have found that MAE extraction improves the efficiency of the extraction of polyphenols and caffeine from green tea leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Extraction under MW has been used for the extraction of bioactive compounds and essential oils from the leaves of rosemary and (Bousbia et al, 2009;Dai et al, 2010), extraction of taxanes from Taxus biomass (Mattina et al, 1997), extraction of ergosterol and fatty acids from fungal hyphae and spores, mushrooms, filtered air, artificially contaminated corn, naturally contaminated grain dust, and soil and the extraction of azadirachtinrelated limonoids from neem seed kernel (Young 1995;Dai et al, 1999). MAE was successfully applied in laboratory scale because faster, ecocompatible (less solvent required), repeatable and very effective (Pérez-Serradilla et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many research studies have been done in the developments of MAE methods for the extraction, such as extraction of taxanes from Taxus biomass (Mattina, Berger, & Denson, 1997), extraction of saikosaponins from Bupleurum falcatum root (Kwon, Choi, Chung, & Lee, 2006), extraction of anticancer drug camptothecin from Nothapodytes foetida (Fulzele & Satdive, 2005), extraction of essential oil from Cardamom (Marie, Jacqueline, Steven, Willem, & Farid, 2007), extraction of ginsenosides from ginseng root (Youn, Ming, & Yuan, 2003), extraction of azadirachtin-related limonoids from neem seed kernel (Dai, Yaylayan, Raghavan, & Parè, 1999), extraction of felodipine tablets (Eskilsson, Bjö rklund, Matheson, Karlsson, & Torstensson, 1999), extraction of glycyrrhizic acid from licorice roots (Pan, Liu, Jia, & Shu, 2000) and extraction of tea polyphenols and tea caffeine from green tea leaves (Pan, Niu, & Liu, 2002).…”
Section: Introductionmentioning
confidence: 99%